Inheritance and field performance of transgenic Korean Bt rice lines resistant to rice yellow stem borer - Kim, Songjin; Kim, Choljun; Li, Wonnam; Kim, Tokyong; Li, Yongsu; Zaidi, Mohsin Abbas; Altosaar, Illimar (Euphytica, 2008)
Transgenic Korean rice plants containing the cry1Ab gene were developed for resistance against yellow stem borer (Scirpophaga incertulas, YSB). More than 100 independent transgenic lines from three Korean varieties (P-I, P-II and P-III) were generated. The amount of Cry1Ab in transgenic T₀ plants was as high as 2.88% of total soluble proteins. These levels were sufficient to cause 100% mortality of YSB larvae. The majority of T₁ transgenic lines originated from the varieties P-I and P-II followed a Mendelian fashion of segregation. Deviation from the expected segregation ratio was observed in a small number of the transgenic lines of P-I and P-II origins. However, this deviation was primarily observed in the P-III originated lines. Segregation analysis of the T₁ generation indicated that 1-3 copies of the cry1Ab gene were integrated into the genome of the majority of the transgenic lines originating from varieties P-I and P-II. Stunted and semi-fertile mutants were observed in some transgenic lines. These aberrations were either independent or closely linked to the introduced cry1Ab gene loci in different transgenic lines. Reduction in GUS expression levels and loss of toxicity against YSB larvae were found in some transgenic lines. The transgenic T₃ and T₄ lines causing 100% mortality of third instar YSB larvae in the lab were completely protected in the field. Analysis of important yield components on nine selected transgenic lines indicated that stem length, panicle length, grain number per panicle, and seed setting rates were reduced in transgenic plants compared to those in non-transgenic parental rice lines. Number of panicles per cluster, however, was significantly higher in transgenic plants. The numerical value of the average yield was in general greater in the controls than in all the transgenic lines, indicating some 'yield drag'. Since some selected lines were highly resistant to the YSB with good yielding potential, they offer effective potential for use in insect resistance management programs.